Pusat Kecantikan Muslimah Di Pekanbaru Dengan Pendekatan Arsitektur Perilaku - Laili Dwi Annisa; Ratna Amanati; Pedia Aldy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Body treatment has become a necessary that can not be separated from women. It because Allah has created the creatures in perfect condition, so human should be grateful. A way to begrateful is keeping and caring of herselves. Muslimah beauty center accommodates the concentrated to make a person looks interesting, beautiful, clean, and health. Muslimah beautycenter adhere to Islamic law. The method transformed akhlakul karimah into architectural form using meaning transformation. Architectural behavior aspects that be applied are privacy,territoriality and personal space. Akhlakul Karimah aspects that be applied are hijab, simplicity, giving, fairness, Ukhuwah Islamiah, and avoid unexpected view. Application of the concept iscontained in setting and circulation space. Privacy using partitions or wall, so the privacy of users can be maintained. That is to keep the views outer room into the inner room. Then, provided asimulation and demonstration space to spend the waiting time. It can influence visitors interactions with other people to keep Ukhuwah Islamiyah. Simplicity be applied with linier circulation. Giving and simplicity concept be applied with mass transformation using substractive and additive from circle, square, and triangle. Fairness be applied with radial balancing.Keywords: Muslimah Beauty Centre, Behavior Architecture, Akhlakul Karimah, Meaning Transformation